Co-Infection of Scrub Typhus and Human Granulocytic Anaplasmosis in Korea, 2006 - Kim, Jeong-Han (J Korean Med Sci, 2019)
BACKGROUND: Scrub typhus, severe fever with thrombocytopenia syndrome (SFTS) and human granulocytic anaplasmosis (HGA) are important arthropod-borne infectious diseases in Korea and share a common point that they are transmitted by arthropod bites mostly during outdoor activities and there are considerable overlaps of epidemiologic and clinical features at presentation. We investigated the co-infection of these infections. METHODS: The study subjects were patients with laboratory-confirmed scrub typhus who were enrolled retrospectively in 2006. SFTS virus (SFTSV) infection was confirmed by a reverse transcriptase polymerase chain reaction (PCR) to amplify partial L segment of SFTSV for molecular diagnosis. HGA was confirmed by a nested PCR to amplify 16S rRNA gene of Anaplasma phagocytophilum. Direct sequencing of the positive PCR products was performed. Clinical features of co-infected subjects were described. RESULTS: One-hundred sixty-seven patients with scrub typhus were included in the analysis. Co-infection of A. phagocytophilum was identified in 4.2% of scrub typhus patients (7/167). The route of co-infection was uncertain. The co-infected patients had not different clinical manifestations compared to the patients with scrub typhus only. All the study subjects were negative for SFTSV. CONCLUSION: We found retrospective molecular evidence of the co-infection of scrub typhus and HGA in Korea. HGA may be more prevalent than expected and need to be considered as an important differential diagnosis of febrile patients in Korea.